Especialização da agricultura na Região Corede Fronteira Oeste do Rio Grande do Sul: uma análise geográfica da produção de arroz, soja, milho e trigo - Teichmann, Jaqueline Bonoto de Garcia (2012)
This study aims to analyze in the geographical category rural space the agricultural production of the territory belonging to the region COREDE Fronteira Oeste do RS, through the contemporaneous acceleration, due to the Tecnic-Scientific-Informacional period following the globalization process f the economics. This region COREDE was analyzed from the intensification of the diffusion of modernization of fixed and flows and viewed as a functional place of spatial circuits of production and cooperation circles of agricultural production. Thus, it is understood that the region since past times os its production and reproduction strives to achieve new tecnological levels. Nowadays it reveals the investiments in advanced tecnology and determines this dynamic as a condition to ensure the production of other complexes that interact with it. The research standards pursued the methodology attending a critical comparative analysis. However, in this procedure it was decided to adopt two methods of investigation, a mixed qualitative and quantitative scheme to obtain the information. In this study, the combination of both criteria was considered essentially important to reach this purpose to offer a representation of the regional reality in nowadays and meet the formulated objectives. The data analysis showed the importance of the studied crops in the investigated region. Nevertheless, rice cultivation has been in the last decades the main agricultural production according to the analysis of historical research and qualitative assay. Today, rice production stands out compared to other crops produced. The increase in this production in the region and its maintenance identifies the specialization of the farming business. The specialization comes from the existence of an entire material and social structure formed by flows and fixed, built prioritizing the cultivation of rice, but serving other cultures, as soybean, corn and weath. The dynamics observed in the study area allowed to accept the idea that the current period reveals the region as a globalized space, and also that the region COREDE Fronteira Oeste is unique in its singularities. These arguments reinforce the idea of single space, uniqueness.